Performance Pay and Multidimensional Sorting - Productivity, Preferences and Gender - Thomas Dohmen; Armin Falk (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2011)
This paper studies the impact of incentives on worker self-selection in a controlled laboratory experiment. Subjects face the choice between a fixed and a variable payment scheme. Depending on the treatment, the variable payment is a piece rate, a tournament or a revenue-sharing scheme. We find that output is higher in the variable pay schemes (piece rate, tournament, and revenue sharing) compared to the fixed payment scheme. This difference is largely driven by productivity sorting. In addition personal attitudes such as willingness to take risks and relative self-assessment as well as gender affect the sorting decision in a systematic way. Moreover, self-reported effort is significantly higher in all variable pay conditions than in the fixed wage condition. Our lab findings are supported by an additional analysis using data from a large and representative sample. In sum, our findings underline the importance of multi-dimensional sorting, i.e., the tendency for different incentive schemes to systematically attract people with different individual characteristics.
urn:nbn:de:bvb:19-epub-13194-1
Keywords: J3; M52; C91; D81; J16; 330; Sorting; Incentives; Piece Rates; Tournament; Revenue-Sharing; Risk Preferences; Social Preferences; Gender; Experiment; Field Evidence; Leistungsentgelt; Lohnstruktur; Geschlecht; Risikopräferenz; Entscheidungstheorie; Test